Genome-wide identification and tissue expression pattern analysis of TPS gene family in soybean (Glycine max) - Li, Huanli; Zhang, Xiaoling; Yang, Qinli; Shangguan, Xiaoxia; Ma, Yanbin (Frontiers in Plant Science, 2024)
The terpene synthase (TPS) plays a pivotal roles in plant growth, development, and enhancing resilience against environmental stresses. Despite this, the bioinformatics analysis of the TPS family gene in soybean (Glycine max) is lacking. In this study, we investigated 36 GmTPS members in soybean, exhibiting a diverse range of protein lengths, spanning from 144 to 835 amino acids. A phylogenetic tree was constructed from these GmTPS genes revealed a classification into five distinct subgroups: Group1, Group2, Group3, Group4 and Group5. Notably, within each subgroup, we identified the motifs of GmTPS proteins were similar, although variations existed among different subfamilies. Gene duplication events analysis demonstrated that TPS genes expand differently in G. max, A. thaliana and O. sativa. Among, both tandem duplication and Whole genome duplication contributive to the expansion of TPS genes in G. max, and Whole genome duplication played a major role. Moreover, the cis-element analysis suggested that TPS is related to hormone signals, plant growth and development and environmental stress. Yeast two-hybrid (Y2H) assay results indicated TPS protein may form heterodimer to function, or may form complex with P450 proteins to function.RNA-seq results revealed a higher higher expression of most GmTPS genes in flowers, suggesting their potential contribution to flower development. Collectively, these findings offer a provide a holistic knowledge of the TPS gene family in soybean and will facilitate further characterization of TPSs effectively.